Contested Development Paths and Rural communities: Sustainable Energy or Sustainable Tourism in Iceland? - Anna Dóra Sæþórsdóttir; C. Michael Hall (Sustainability, 2019)
The Icelandic economy has transitioned from being dependent on fishing and agriculture to having tourism and refined aluminum as its main exports. Nevertheless, the new main industries still rely on the country’s natural resources, as the power intensive industry uses energy from rivers and geothermal areas whereas tourism uses the natural landscape, where geysers, waterfalls and thermal pools are part of the attraction to visitors. Although both industries claim to contribute to sustainability they utilize the same resources, and land-use conflicts can be expected, illustrating the contestation that can occur between different visions and understandings of sustainability. This paper focuses on the attitudes of Icelandic tourism operators towards power production and proposed power plants using data from questionnaires and face-to-face interviews. Results show that the majority of Icelandic tourism operators assume further power utilization would be in conflict with nature-based tourism, and they are generally negative towards all types of renewable energy development and power plant infrastructure. Respondents are most negative towards transmission lines, reservoirs and hydro power plants in the country’s interior Highlands. About 40% of the respondents perceive that existing power plants have negatively affected tourism, while a similar proportion think they had no impact. According to the respondents, the two industries could co-exist with improved spatial planning, management and inter-sectoral cooperation.